Legionellosis and Lung Abscesses: Contribution of Legionella Quantitative Real-Time PCR to an Adapted Followup. (3rd June 2013) - Descours, G.; Tellini, C.; Flamens, C.; Philit, F.; Celard, M.; Etienne, J.; Lina, G.; Jarraud, S.
Abstract : We report a case of severe Legionnaires' disease (LD) complicated by a lung abscess in an immunocompetent patient who required ECMO therapy and thoracic surgery. The results of repeated Legionella quantitative real-time PCR performed on both sera and respiratory samples correlated with the LD severity and the poor clinical outcome. Moreover, the PCR allowed for the detection of Legionella DNA in the lung abscess specimen, which was negative when cultured for Legionella . This case report provides a logical basis for further investigations to examine whether the Legionella quantitative PCR could improve the assessment of LD severity and constitute a prognostic marker.